Fluorescence Detection of Pb2+ in Environmental Water Using Biomass Carbon Quantum Dots Modified with Acetamide-Glycolic Acid Deep Eutectic Solvent - Shiwen Xing; Keyang Zheng; Lei Shi; Kaiming Kang; Zhixiao Peng; Xiaojie Zhang; Baoyou Liu; Huilong Yang; Gang Yue (Molecules, 2024)
In this study, a novel green fluorescent probe material, nitrogen-doped carbon quantum dots (N-CQDs), was prepared by a one-step hydrothermal synthesis method using walnut green skin as a carbon source and acetamide-glycolic acid deep eutectic solvent (AGADES) as a modifier. By covalent coupling, the amide chromophore in AGADES is designed to cover the surface of walnut green skin carbon quantum dots (W-CQDs), forming a fluorescence energy resonance effect and improving the fluorescence performance of the carbon quantum dots. The prepared N-CQDs have a uniform particle size distribution, and the fluorescence quantum efficiency has increased from 12.5% to 32.5%. Within the concentration range of 0.01~1000 μmol/L of Pb2+, the linear detection limit is 1.55 nmol/L, which can meet the trace detection of Pb2+ in the water environment, and the recycling rate reaches 97%. This method has been successfully applied to the fluorescence detection and reuse of Pb2+ in actual water bodies, providing new ideas and methods for the detection of heavy metal ions in environmental water.